Analysis of Water Availability Model of Ngunut Sub-Watershed, Upper Bengawan Solo - Noor, Dewi Lies (Forum Geografi, 1996)
The aims of this research is 1) formulating a model for water availability in order to know the input-output process in Ngunut Sub Watershed; 2) knowing the condition of water availability components for each landuse; 3) determining the best alternative landuse in Ngunut sub watershed. Data used in this researh were mean rainfall and temperature in ten years, water content in soil, groundwater flow, crop coefisien, landuse area, and the agricultural production value. There are 3 main outcomes of this research. The first, one is in form of software, concerning the water availability model in Ngunut Sub watershed. The second outcome, for mixed plantation, infiltration, water storage, and percolation had high values but surface runoff has a low value. For the rice field, evapotranspiration has the highest value, with interception, infiltration, and water storage having low values. For the dry fields; interception had the highest value. For the settlement, surface runoff had the biggest value. The third outcome, is that the landuse changes from irrigated rice fields and dry fields to form of mixed plantations, constitute the best alternatives in the spatial organization of Ngunut watershed, whose values are high.